The stable isotope composition of nitrogen and carbon and elemental contents in modern and fossil seabird guano from Northern Chile - Marine sources and diagenetic effects. - Friedrich Lucassen; Wolfgang Pritzkow; Martin Rosner; Fernando Sepúlveda; Paulina Vásquez; Hans Wilke; Simone A Kasemann (PLoS ONE, 2017)
Seabird excrements (guano) have been preserved in the arid climate of Northern Chile since at least the Pliocene. The deposits of marine organic material in coastal areas potentially open a window into the present and past composition of the coastal ocean and its food web. We use the stable isotope composition of nitrogen and carbon as well as element contents to compare the principal prey of the birds, the Peruvian anchovy, with the composition of modern guano. We also investigate the impact of diagenetic changes on the isotopic composition and elemental contents of the pure ornithogenic sediments, starting with modern stratified deposits and extending to fossil guano. Where possible, 14C systematics is used for age information. The nitrogen and carbon isotopic composition of the marine prey (Peruvian anchovy) of the birds is complex as it shows strong systematic variations with latitude. The detailed study of a modern profile that represents a few years of guano deposition up to present reveals systematic changes in nitrogen and carbon isotopic composition towards heavier values that increase with age, i.e. depth. Only the uppermost, youngest layers of modern guano show compositional affinity to the prey of the birds. In the profile, the simultaneous loss of nitrogen and carbon occurs by degassing, and non-volatile elements like phosphorous and calcium are passively enriched in the residual guano. Fossil guano deposits are very low in nitrogen and low in carbon contents, and show very heavy nitrogen isotopic compositions. One result of the study is that the use of guano for tracing nitrogen and carbon isotopic and elemental composition in the marine food web of the birds is restricted to fresh material. Despite systematic changes during diagenesis, there is little promise to retrieve reliable values of marine nitrogen and carbon signatures from older guano. However, the changes in isotopic composition from primary marine nitrogen isotopic signatures towards very heavy values generate a compositionally unique material. These compositions trace the presence of guano in natural ecosystems and its use as fertilizer in present and past agriculture.